2022
DOI: 10.1101/2022.01.20.477041
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A molecular dynamics study of antimicrobial peptide translocation across the outer membrane of Gram-negative bacteria

Abstract: With rising bacterial resistance, antimicrobial peptides (AMPs) have been widely investigated as potential antibacterial molecules to replace conventional antibiotics. Our understanding of the molecular mechanism for membrane disruption are largely based on AMP interactions with the inner phospholipid bilayers of both Gram-negative and Gram-positive bacteria. Mechanisms for AMP translocation across the outer membrane of Gram-negative bacteria composed of lipopolysaccharides and the asymmetric lipid bilayer ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…58 Our recent study reports the free energy landscapes for CM15 peptide (cecropin A and melittin residues) for its translocation across the complex outer membrane of E. coli. 59 Although the interactions of melittin with lipid membranes have been extensively studied and several molecular insights have emerged [60][61][62][63][64] only few studies have reported the inter- The number of contacts made by melittin with individual units of peptidoglycans for S. aureus and E. coli models. The contacts are calculated using a distance cutoff of 0.5 nm, and averaged over 500 ns long trajectories as well as averaged over the melittin peptides.…”
Section: Interactions Of Peptidoglycans With Melittinmentioning
confidence: 99%
See 1 more Smart Citation
“…58 Our recent study reports the free energy landscapes for CM15 peptide (cecropin A and melittin residues) for its translocation across the complex outer membrane of E. coli. 59 Although the interactions of melittin with lipid membranes have been extensively studied and several molecular insights have emerged [60][61][62][63][64] only few studies have reported the inter- The number of contacts made by melittin with individual units of peptidoglycans for S. aureus and E. coli models. The contacts are calculated using a distance cutoff of 0.5 nm, and averaged over 500 ns long trajectories as well as averaged over the melittin peptides.…”
Section: Interactions Of Peptidoglycans With Melittinmentioning
confidence: 99%
“…58 Our recent study reports the free energy landscapes for CM15 peptide (cecropin A and melittin residues) for its translocation across the complex outer membrane of E. coli . 59…”
Section: Structural Propertiesmentioning
confidence: 99%